Pigmentation abnormality in the blotched round ray Urotrygon asterias (Myliobatiformes: Urotrygonidae): first case of partial xanthism within the family - Argüello-Rojas, Sebastián (2026)
Introduction: Malpigmentation or pigment disorders can result from either a deficiency or an excess of pigments and have been reported in a wide variety of fish taxa. Color abnormalities are rare among elasmobranchs. Among nearly 1 250 known species, only 22 cases of malpigmentations as albinism and leucism, have been reported, most involving sharks and rarely batoids. Xanthochromism is a rare pigmentation disorder characterized by a yellow-orange coloration caused by multiple factors. This condition has been scarcely reported in elasmobranchs, with only seven known cases, five of them in batoids. Objectives: Here, we present the first record of xanthochromism in the blotched round ray Urotrygon asterias, and the first within the family Urotrygonidae. Methods: One juvenile specimen was captured two times during a monitoring program at Playa Manzanillo, El Jobo, Guanacaste, Costa Rica, and photographic identification confirmed it was the same individual. Additionally, morphometric measurements of the individual were taken to assess whether it had grown. Results: The recapture of this specimen indicates that xanthochromism does not necessarily compromise short-term survival. Potential causes of the condition include genetic mutations, diet, gestation disorders, or environmental factors, such as contamination. Playa Manzanillo exhibits evidence of anthropogenic impacts, including fishing waste and pollutants, which may influence local ichthyofauna health. Conclusions: This finding expands the understanding of pigmentation anomalies in batoids and highlights the need for further research to assess the environmental drivers of morphological abnormalities, including pigmentation, in elasmobranchs. Such studies are crucial for evaluating the ecological and conservation implications of these disorders in the Ester Tropical Pacific.